2010
DOI: 10.1007/s00540-010-0985-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of aspiration during anesthesia in patients with congenital insensitivity to pain with anhidrosis: case reports and review of the literature

Abstract: Congenital insensitivity to pain with anhidrosis (CIPA) is a rare autosomal recessive disease, characterized by episodes of unexplained fever, anhidrosis, pain insensitivity despite intact tactile perception, self-mutilating behavior, mental retardation, and autonomic nervous system (ANS) abnormalities. We present a case series of three patients with CIPA who underwent semielective orthopedic surgery under general anesthesia complicated by intraoperative regurgitation, and subsequent aspiration in two of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Moreover, perioperative antibiotic coverage and aggressive pulmonary hygiene are also crucial to prevent postoperative pulmonary complications in ID patients with high susceptibility, including congenital central alveolar hypoventilation syndrome (Ondine's curse) [38], Langer-Giedion syndrome [39], mucopolysaccharide storage disorders [40] and cri du chat syndrome [41]. ID patients with congenital insensitivity to pain with anhidrosis should be managed as “full stomach” patients to prevent perioperative regurgitation and aspiration, because their gastric emptying is delayed due to autonomic nervous system dysfunction [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, perioperative antibiotic coverage and aggressive pulmonary hygiene are also crucial to prevent postoperative pulmonary complications in ID patients with high susceptibility, including congenital central alveolar hypoventilation syndrome (Ondine's curse) [38], Langer-Giedion syndrome [39], mucopolysaccharide storage disorders [40] and cri du chat syndrome [41]. ID patients with congenital insensitivity to pain with anhidrosis should be managed as “full stomach” patients to prevent perioperative regurgitation and aspiration, because their gastric emptying is delayed due to autonomic nervous system dysfunction [42].…”
Section: Discussionmentioning
confidence: 99%
“…13 In this study, we observed only 2 cases of regurgitation with aspiration and 1 case of regurgitation without aspiration, representing about 0.8% of the cases. It has previously been suggested that all CIPA patients should be considered having a “full stomach,” regardless of their nil per os status, because of their risk of aspiration.…”
Section: Discussionmentioning
confidence: 49%
“…The autonomic nervous system abnormalities are common in patients with CIPA, leading to disturbances in gastric myoelectric activity and therefore gastric emptying delay and dyspeptic symptoms, predisposing CIPA patients to an increased risk of regurgitation and aspiration when they are anesthetized [8,9]. In our case the throat reflex was maintained during TIVA with spontaneous respiration via facemask, avoiding aspiration if the patient regurgitated.…”
Section: Discussionmentioning
confidence: 79%
“…In our case the throat reflex was maintained during TIVA with spontaneous respiration via facemask, avoiding aspiration if the patient regurgitated. Previous cases report demonstrated that laryngeal mask airway (LMA) is not appropriate for the airway management of CIPA patients, leading regurgitation, aspiration and even hypoxic cardiac arrest [9]. For those patients, surgical procedures can be done with superficial anesthesia but the gag reflex from stimulation of the pharynx with LMA may not be inhibited.…”
Section: Discussionmentioning
confidence: 99%